Geometric Typology of an Organically Developed Commercial Corridor: A Case Study of Anggrek Street, Maumere - Cornelia Hildegardis (Institut Teknologi dan Bisnis Ahmad Dahlan, 2026)
Organically developed commercial areas commonly exhibit diverse building geometries that influence the spatial character and visual quality of the urban environment. This study aims to identify and analyze the geometric typology of buildings along the Anggrek Street commercial corridor in Sikka Regency based on five geometric attributes: building position, orientation, basic form, form transformation, and visual inertia. A descriptive qualitative approach was employed through field observations of five representative buildings selected using purposive sampling to capture the diversity of geometric characteristics within the study area. The analysis adopted an architectural typology approach to examine the relationships among these geometric attributes in shaping the spatial character of the commercial corridor. The results indicate that the corridor is predominantly composed of semi-attached and attached building typologies, reflecting increasing land-use intensity. Building orientation facing the street corridor enhances urban legibility and the visibility of commercial activities. The basic forms are primarily rectangular and cuboid, which have evolved through additive and subtractive transformations in response to spatial requirements. Differences in visual inertia are influenced by mass composition, color, façade articulation, and signage. The findings demonstrate that the spatial character of the corridor is shaped primarily by geometric transformation rather than variations in basic building form. Unlike previous typological studies that primarily focus on planned commercial districts, this study develops an integrated framework consisting of five geometric attributes to interpret organically developed commercial corridors. This study contributes to the advancement of geometric typology research by providing empirical insights into organically developed commercial corridors in small emerging cities, offering a conceptual basis for future urban design and corridor planning.